The poor design of clinical trials of statins in oncology may explain their failure – Lessons for drug repurposing. (September 2018) - Abdullah, Marwan I.; de Wolf, Elizabeth; Jawad, Mohammed J.; Richardson, Alan
Highlights: Significant preclinical and retrospective clinical studies suggest statins are effective in cancer but prospective trials have failed. Statin type, dose, dose interval, and patient diet have not been adequately considered. An improved trial design for statins in cancer is proposed. Clinical trial design during drug repurposing studies needs careful consideration. Abstract: Statins are widely used to treat hypercholesterolaemia. However, by inhibiting the production of mevalonate, they also reduce the production of several isoprenoids that are necessary for the function of small GTPase oncogenes such as Ras. As such, statins offer an attractive way to inhibit an "undruggable" target, suggesting that they may be usefully repurposed to treat cancer. However, despite numerous studies, there is still no consensus whether statins are useful in the oncology arena. Numerous preclinical studies have provided evidence justifying the evaluation of statins in cancer patients. Some retrospective studies of patients taking statins to control cholesterol have identified a reduced risk of cancer mortality. However, prospective clinical studies have mostly not been successful. We believe that this has occurred because many of the prospective clinical trials have been poorly designed. Many of these trials have failed to take into account some or all of the factors identified in preclinical studies that are likely to be necessary for statins to be efficacious. We suggest an improved trial design which takes these factors into account. Importantly, we suggest that the design of clinical trials of drugs which are being considered for repurposing should not assume it is appropriate to use them in the same way as they are used in their original indication. Rather, such trials deserve to be informed by preclinical studies that are comparable to those for any novel drug.